Community Structure of Seagrass Semak Daun Island and Kotok Kecil Island, Seribu Island, Jakarta - Sri Handayani; Indraswati Pratiwi; Dwi Andayaningsih (Universitas Nasional Jakarta, 2022)
Seagrass is a shallow waters ecosystem. Research on the structure of the seagrass community has been conducted on Semak Daun Island and Kotok Kecil Island, Thousand Islands, Jakarta. Semak Daun Island includes the residential zone where is a lot of human activity, and Kotok Kecil Island is a part of the utilization zone. This study aimed to determine the structure of the seagrass community on Semak Daun Island and Kotok Kecil Island. Data were collected using the line transect and quadratic methods; one island is divided into 4 stations that are assigned into 3 transects with 25 m length from each station, and 50 meters straight line is drawn from each transect, and a plot 1 x 1 m is laid out every 10 meters. The results showed that the species composition on Semak Daun Island (4 species, 2 families) was higher than on Kotok Kecil Island (2 species, 2 families). The Similarity Index between the two islands was at the same level. The seagrass diversity index on Semak Daun Island was in the medium category, and the diversity of seagrass species on Kotok Kecil Island is low. Frequency, Density, Coverage, and Important Value Index on both islands were the same, Thalassia hemprichii had the highest yield compared to other species on both islands, whereas the smallest on Semak Daun Island was Halophila ovalis and the smallest on Kotok Kecil Island was Halodule uninervis.